2016
DOI: 10.3389/fpls.2016.01241
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Regulators of Plant-Hemipteran Interactions: Micromanagers with Versatile Roles

Abstract: Non-coding small RNAs (sRNAs) in plants have important roles in regulating biological processes, including development, reproduction, and stress responses. Recent research indicates significant roles for sRNA-mediated gene silencing during plant-hemipteran interactions that involve all three of these biological processes. Plant responses to hemipteran feeding are determined by changes in the host transcriptome that appear to be fine-tuned by sRNAs. The role of sRNA in plant defense responses is complex. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 168 publications
(230 reference statements)
0
20
0
Order By: Relevance
“…Few studies have reported the use of combined miRNA and mRNA expression profiles to analyze the responses of herbivore insects in plants, excluding studies on aphidinduced miRNA expression [35]. This study was the first to report the combined analysis of miRNA and mRNA expression profiles in BPH-infested rice, enhancing our understanding of the regulatory mechanisms of miRNA-mRNA in rice after BPH attack.…”
Section: Discussionmentioning
confidence: 96%
“…Few studies have reported the use of combined miRNA and mRNA expression profiles to analyze the responses of herbivore insects in plants, excluding studies on aphidinduced miRNA expression [35]. This study was the first to report the combined analysis of miRNA and mRNA expression profiles in BPH-infested rice, enhancing our understanding of the regulatory mechanisms of miRNA-mRNA in rice after BPH attack.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence is accumulating for a role of miRNAs in the plant responses to biotic stress 14 18 . In plant-insect interactions, aphid-induced small RNA expression has been studied in many plants 48 . This is the first report of the miRNA response to herbivore insect in rice.…”
Section: Discussionmentioning
confidence: 99%
“…A recently developed pathogen control strategy, which is called host-induced gene silencing (HIGS), is based on generating transgenic plants that express pathogen-specific dsRNA to trigger silencing of essential genes in insects, fungi and other pests ( Nunes & Dean, 2012 ; Koch & Kogel, 2014 ; Weiberg & Jin, 2015 ). Importantly, recent reports show that not only artificial transgenic HIGS dsRNAs, but also plant endogenous dsRNAs can be actively transported into insect cells; however, the functional consequences of consuming these dietary-derived plant dsRNAs for the insects remain to be clarified ( Ivashuta et al, 2015 ; Sattar & Thompson, 2016 ). The natural dsRNA transfer from plants to insects was reconstituted in numerous studies of insect feeding on substrates containing artificial insect-specific dsRNAs.…”
Section: Discussionmentioning
confidence: 99%